2019
DOI: 10.1002/cjp2.128
|View full text |Cite
|
Sign up to set email alerts
|

Disparate cell proliferation and p53 overexpression in colonic crypts with normal epithelial lining found below the neoplastic canopy of conventional adenomas

Abstract: We previously found colonic crypts with normal epithelial lining but with corrupted shapes (NECS) beneath the adenomatous tissue of conventional adenomas (CoAs). Here we assessed the distribution of proliferating cells (PCs) and explored the possible occurrence of p53‐upregulated cells in the NECS in a cohort of CoAs. Sections from 70 CoAs and from 12 normal colon segments were immunostained with the proliferation marker Ki67. In 60 of the 70 CoAs, additional sections were immunostained for the tumor suppresso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 34 publications
(80 reference statements)
0
10
0
Order By: Relevance
“…51 Thus, the apparently normal epithelium of the CCS beneath the adenomatous tissue of sporadic polypoid conventional adenomas concurred with an unprecedented relocation of the natural PC domains, and with p53-upregulated cells, suggesting thereby, possible mounting somatic mutations in the CCS of those neoplastic lesions. 50 In another investigation, this time with 48 non-polypoid adenomas, we found that 88% of the CCS exhibited haphazardly asymmetrically-distributed PC-domains, 8% continuous PCdomains in one or both slopes of the CCS, and 4%, asymmetrically-haphazardly distributed single PC. 46 The CCS in 29% of the 48 non-polypoid adenomas also showed p53-upregulated often as single cells.…”
Section: Non-dysplastic Crypts With Ccs Showingmentioning
confidence: 73%
See 4 more Smart Citations
“…51 Thus, the apparently normal epithelium of the CCS beneath the adenomatous tissue of sporadic polypoid conventional adenomas concurred with an unprecedented relocation of the natural PC domains, and with p53-upregulated cells, suggesting thereby, possible mounting somatic mutations in the CCS of those neoplastic lesions. 50 In another investigation, this time with 48 non-polypoid adenomas, we found that 88% of the CCS exhibited haphazardly asymmetrically-distributed PC-domains, 8% continuous PCdomains in one or both slopes of the CCS, and 4%, asymmetrically-haphazardly distributed single PC. 46 The CCS in 29% of the 48 non-polypoid adenomas also showed p53-upregulated often as single cells.…”
Section: Non-dysplastic Crypts With Ccs Showingmentioning
confidence: 73%
“…Those unexpected findings suggested that the CCS in the stalk were possibly undergoing somatic mutation. 50…”
Section: Crypts With Ccs In the Mucosa Of The Stalkmentioning
confidence: 99%
See 3 more Smart Citations